Improved laccase production by Trametes versicolor using Copper-Glycyl-L-Histidyl-L-Lysine as a novel and high-efficient inducer - Wang, Feng; Yu, Xiaolei; Yu, Zhuo; Cui, Yi; Xu, Ling; Huo, Shuhao; Ding, Zhongyang; Zhao, Liting; Du, Lizhi; Qiu, Yanguo (Frontiers in Bioengineering and Biotechnology, 2023)
A highly efficient strategy using Copper-Glycyl-L-Histidyl-L-Lysine (GHK-Cu) as a novel inducer was developed to enhance laccase production by Trametes versicolor. After medium optimization, laccase activity increased by 12.77-fold compared to that without GHK-Cu. The laccase production of 1113.8 U L−1 was obtained by scaling-up culture in 5-L stirring tank. The laccase production induced by CuSO4 was poorer than that of GHK-Cu at the same mole concentration. GHK-Cu could increase the permeability of cell membrane with less damage, and it facilitated the adsorption, accumulation, and utilization of copper by fungal cells, which was beneficial for laccase synthesis. GHK-Cu induced better expression of laccase related genes than that of CuSO4, resulting in higher laccase production. This study provided a useful method for induced production of laccase by applying GHK chelated metal ion as a non-toxic inducer, which reduced the safety risk of laccase broth and provided the potential application of crude laccase in food industry. In addition, GHK can be used as the carrier of different metal ions to enhance the production of other metalloenzymes.